Effect of Resin Treatment on the Properties of Veneers at Various Stages - Gupta, R. C.; Jain, D. K. (Indian Forester, 1980)
Nine different species of timbers both from soft and hardwoods were subjected to different stages of resin treatment and curing as is generally done in the case of plywood etc. After each stage of treatment, the physical strength properties eg. Modulus of elasticity, Modulus of regidity and Tensile strength were evaluated. The results show striking similarity in behaviour with only few exceptions. The presence of moisture and wet resin decidedly decrease the strength properties.